A study of the performance and some physical characteristics of N'Dama and West African Shorthorn cattle in the humid forest zone of Ghana - Danso, Y.N. (1980)
Brief study on reproductive and productive performance of N'Dama and West African Shorthorn cattle in Ghana. Data on physical characteristics (colour and physical body measurements); reproductive parameters (age at first calving, mean calving intervals and calving percentage); and productive parameters (average daily gain at birth to 3 months, 3 to 6 months, 6 to 12 months and 12 to 24 months) of both breeds included.